2021
DOI: 10.1016/j.wear.2021.203789
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slide-to-roll ratio and temperature on the tribological behaviour in polymer-steel contacts and a comparison with the performance of real-scale gears

Abstract: This peer reviewed manuscript has been accepted for publications to the Wear. Cite this article as: S. Matkovič, M. Kalin, Effects of slide-to-roll ratio and temperature on the tribological behaviour in polymer-steel contacts and a comparison with the performance of realscale gears, Wear (2021) 477: 203789.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It was shown that POM gears may experience this phenomenon when subjected to loads exceeding 10 Nm at an ambient temperature of approximately 25 • C [18,19]. Apart from abrasive wear, thermal wear is the main wear component for a POM/steel pairing [20]. The wear rate is similar to that of a POM/POM combination [18].…”
Section: Polymer Gearsmentioning
confidence: 99%
“…It was shown that POM gears may experience this phenomenon when subjected to loads exceeding 10 Nm at an ambient temperature of approximately 25 • C [18,19]. Apart from abrasive wear, thermal wear is the main wear component for a POM/steel pairing [20]. The wear rate is similar to that of a POM/POM combination [18].…”
Section: Polymer Gearsmentioning
confidence: 99%
“…Furthermore, it was observed that a plain medium carbon steel (DIN C56E2) showed better surface fatigue resistance than a low alloy high carbon steel (DIN 100Cr6) at similar surface hardness levels if surface induction hardening is applied on the former. Correlation between the tribological behavior of polymer-steel contacts and the performance of real-scale gears was reported [452]. The results showed that tests at 50 °C in slide-roll ratio (SRR)-variable model tribotests can predict the SRR-dependent wear mechanisms along the meshing path in real gears, while the 80 °C tests are too severe, leading to thermal overload.…”
Section: Failure Analysis Multi-dimensional Assessment and Optimizati...mentioning
confidence: 99%
“…In contrast to conventional pin-on-disk tests with pure sliding for tribological test, the variation of slip-roll-ratio (SRR) in the model tribological test mimic different wear mechanisms of real scale gear tests. 168 However, for gear design calculations, the value of wear coefficient of polymers should be obtained from real-scale gear tests. 169 Ghelloudj et al 67 developed a new engineering model to define the evolution of tooth flank wear (wear profile) as a function of number of cycles of driving wheel, the pinion.…”
Section: Classification Of Review Of Polymer Gearingmentioning
confidence: 99%